2017
DOI: 10.1016/j.contraception.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive knowledge and use among women living in the poorest areas of five Mesoamerican countries

Abstract: ObjectiveTo identify factors associated with contraceptive use among women in need living in the poorest areas in five Mesoamerican countries: Guatemala, Honduras, Nicaragua, Panama and State of Chiapas (Mexico).Study designWe analyzed baseline data of 7049 women of childbearing age (15–49 years old) collected for the Salud Mesoamérica Initiative. Data collection took place in the 20% poorest municipalities of each country (July, 2012-August, 2013).ResultsWomen in the poorest areas were very poorly informed ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 17 publications
5
26
0
Order By: Relevance
“…intrauterine device, sterilization, injectables, hormone implants, patches, diaphragms, spermicidal agents, and emergency contraception. Coinciding with previous reports (11,20), women were knowledgeable and supportive of a range of contraceptive methods. However, many informants revealed that their pregnancies were not planned.…”
Section: Current Modern Contraceptive Methods Available In Honduras Isupporting
confidence: 57%
See 2 more Smart Citations
“…intrauterine device, sterilization, injectables, hormone implants, patches, diaphragms, spermicidal agents, and emergency contraception. Coinciding with previous reports (11,20), women were knowledgeable and supportive of a range of contraceptive methods. However, many informants revealed that their pregnancies were not planned.…”
Section: Current Modern Contraceptive Methods Available In Honduras Isupporting
confidence: 57%
“…During the Zika epidemic, women in our study did not mention having received specific information on Zika when they used emergency care and that information on counselling was inconsistent; in fact, information seems to be distributed only during specific campaigns against diseases such as Zika or dengue. Counselling at health facilities is a crucial intervention for the promotion of contraceptive use; however, as seen in our study, visiting a health facility per se does not necessarily mean that a woman would receive counselling (20). Coinciding with another report from Brazil (24), women in our study were not fully aware that Zika could be sexually transmitted and counselling about this issue was limited.…”
Section: Current Modern Contraceptive Methods Available In Honduras Imentioning
confidence: 61%
See 1 more Smart Citation
“…The analysis used data from the 2012 nationally representative population-based household survey conducted using a multistage stratified design described in detail elsewhere [10]. Briefly, a probability sample of 15 households drawn from 1000 randomly selected randomly selected enumeration areas (EAs) was used.…”
Section: Study Design and Samplementioning
confidence: 99%
“…For example, low contraceptive use has been associated with sociodemographic factors such as women coming from rural areas, those with low educational qualification, low socio-economic status, limited knowledge on accessibility, and awareness of contraceptives [9]. Previous findings also associated poor contraceptive usage with poor knowledge [10]. Furthermore, lack or low contraceptive use was associated with the fear of being labelled wayward and promiscuous for carrying or demanding usage of condoms by their partners [11].…”
Section: Introductionmentioning
confidence: 99%